Evaluation of Photoprotective of Gyrinops versteegii (Gilg.) Domke Leaves Extract with Different Solvents and Its Spatial Distribution - Reskyaningsih Parintak; Maryani Maryani; Lisna Hidayati; Nastiti Wijayanti; Tri Rini Nuringtyas (Universitas Sebelas Maret, 2023)
Gyrinops versteegii (Gilg.) Domke is one of the Thymelaeaceous family species with high economic value. The leaf synthesizes secondary metabolites (SMs) supporting herbal medicine, including a class of SMs that serve as sunscreen. However, the SMs are not equally distributed in the plant, depending on the organs, tissues or cell type. This research aimed to determine the spatial distribution of secondary metabolites in the leaves, especially in the epidermis and mesophyll tissues. The epidermis tissues were separated from the mesophyll using the carborundum abrasion (CA) technique, followed by the extraction of SMs using three different polarity solvents, namely methanol, hexane and chloroform. The photoprotective potential was evaluated using the SPF value with the spectrophotometry approach. Subsequently, the phytochemical analysis was done for the total tannin, flavonoid, and phenols content. The results showed that the highest SPF value was observed in the methanol epidermis extract with SPF value of 8.61, followed by methanol mesophyll extract (4.52), chloroform epidermis extract (3.97), chloroform mesophyll extract (2.52) and hexane epidermis extract (0.60) and hexane mesophyll extract (0.16). Total phenolic content (flavonoid, tannin and phenol) in epidermis extract with methanol solvent was higher (12.347 ± 0.652 mg GAE/g DW), followed by extract with chloroform and hexane solvents. The total phenolic content (flavonoid, tannin and phenol) of mesophyll extract with methanol solvent showed the highest content, followed by chloroform mesophyll and hexane extracts. The results of the histochemical analysis showed that photoprotective compounds accumulate in the epidermis and mesophyll tissue of the leaf of G. versteegii.